SISTEM INFORMASI PEMETAAN DAN PENYULUHAN COVID-19 PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN LABUHANBATU UTARA - Febriansyah Marwan; Dody Hidayat; Budi (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2020)
The spread of the Corona virus or what is called COVID-19 has caused hundreds of thousands of victims to die around the world. The need for fast and accurate information is a top priority for the community to deal with a pandemic situation like this, especially in North Labuhanbatu district. In this case, the delivery of information by the North Labuhanbatu Regency Communication and Information Office is carried out using the socialization method. This method is considered right on target, but with the increasing spread of Covid-19 in the North Labuhanbatu district, a faster and more effective method is needed in conveying information to the public to prevent additional casualties. The internet and the web as new breakthroughs in information media are expected to make it easier for people to get fast and accurate information. Apart from that, the presence of the internet and the web has also given rise to new media in geospatial mapping and WebGIS. WebGIS is a web-based Geographical Information System which consists of several interrelated components. WebGIS is a combination of mapping graphic design, digital maps with geographic analysis, computer programming, and a database that is connected to one part of web design and web mapping. The existence of WebGIS can help the Office of Communication and Informatics in North Labuhanbatu regency in delivering fast and accurate information to the people of North Labuhanbatu district.